Effect of Covid-19 isolation on syphilis and AIDS cases in the Municipality of Fernandopolis, São Paulo State, Brazil (Research, Society and Development, 2024)
At the beginning of 2020, the world was struck by COVID-19, a disease caused by SARS-CoV-2. To contain the spread of the virus, Brazil adopted social isolation measures due to the high transmissibility and lethality of the disease. This study aimed to assess the effect of isolation in 2020 and 2021 on the incidence rates of syphilis and HIV/AIDS in the municipality of Fernandópolis, SP. A retrospective epidemiological study with a quantitative approach was conducted, utilizing data from the Ministry of Health's Epidemiological Indicators Panel, related to the Health Disease Notification System (SINAN) for the period from 2019 to 2021. The analysis compared data from one year before the pandemic with the years during isolation. Sociodemographic and epidemiological variables were analyzed using descriptive statistics techniques, considering the absolute and relative frequency of the data. In reported cases of syphilis, there was a predominance of males, white race, age group of 20 to 39 years, and complete secondary education. There was an increase in cases from 2019 to 2020, but a significant decrease in 2021, the year with the highest number of COVID-19 deaths and the longest period of isolation. Regarding AIDS, males prevailed throughout the studied years, with the highest incidence in 2019 and 2021 in the age group of 35 to 49 years and in 2020 between 20 and 34 years. The white race predominated in 2019 and 2020, but there were not enough records in 2021. Educational attainment showed equality among the series, with the highest number of cases in 2020 for complete secondary education. The number of cases increased from 2019 to 2020 but dropped by about 50% in 2021.